Polygenic early‐onset colorectal cancer in pediatric patients. Issue 10 (7th June 2022) - Phen, Claudia; Berens, Donovan; Moriarty, Kelsey; Ng, Kenneth; Sengupta, Anita; Rojas, Isabel
Abstract: Colorectal cancer in the pediatric population is a rare but transpirable phenomenon. The occurrence should prompt suspicion for underlying genetic mutations in the setting of a hereditary cancer predisposition syndrome. In this series, we outline three pediatric patients with colonic adenocarcinoma who were found to have one or more germline mutations. The presence of compound mutations may lead to a hypermutator phenotype resulting in earlier presentation of colorectal cancer in childhood and adolescence. The diagnosis of colorectal cancer in pediatric patients warrants timely recognition, multigene panel testing, genetic counseling for the patient and family, and increased surveillance for intestinal and extra‐intestinal tumors.